A Review on Pongamia pinnata (L.): Traditional Uses, Phytochemistry and Pharmacological Properties - Fugare, Akshay G.; Shete, Rajkumar V.; Adak, Vishal S.; G., Krishna Murthy (Journal of Drug Delivery and Therapeutics, 2021)
Pongamia pinnata (L.) Pierre is one of many plants with different medicinal properties where all its components have been used in the treatment and prevention of many forms of ailments in many countries as traditional medicine. The plant extract shows anti-diarrhoeal, anti-fungal, anti-plasmodial, anti-ulcer, anti-inflammatory, anti-nociceptive, anti-hyperglycaemic, anti-hyperammonic, anti-lipoxidative, anti-oxidant and analgesic activities. For gums, teeth and ulcers, roots are used for cleaning. For bleeding piles, bark is used internally. Traditionally, different parts of the P. pinnata plant are said to be used to treat bronchitis, whooping cough, rheumatism, diarrhea, dyspepsia, flatulence, gonorrhea and leprosy, to name a few. Oil is a source of biodiesel, an alternative, sustainable, nutritious and non-pollutant. The present Knowledge of traditional uses, phytochemistry and pharmacological activities according to parts of the Pongamia pinnata plant is discussed in this study. Keywords: Fabaceae, Pongamia pinnata, Phytochemistry, Pharmacological properties.